An Approach Paper on India's Development as Knowledge Society - Planning Commission (Planning Commission, 2000)
Hon’ble Prime Minister of India, Shri Atal Behari Vajpayee, has recently unveiled a five point agenda for India’s Development as Knowledge Society. The Prime Minister stated “A knowledge based society will enable us to leap-frog in finding new and innovative ways to meet the challenges of building a just and equitable social order and seek urgent solutions” in his inaugural address to delegates attending the ASSOCHAM summit recently held on “India in the knowledge millennium”.
Planning Commission
Planning Commission